Kemampuan Bangsa Merespon Globalisasi dalam Pandangan Islam (The Nation's Ability to Respond the Globalization Based on the Islamic Perspective) - Ace Nurasa; Agus Sumpena; Uus Ruswandi; Mohamad Erihadiana (Potret Pemikiran, 2022)
This study aims to understand the nation's ability to respond the globalization based on the Islamic perspective. It uses a descriptive analysis approach, while the type of exploration is library research. Data is obtained through the study of manuscripts. The results indicate that the consequence of globalization is that the Indonesian people in responding to the negative and positive impacts of globalization, should tend to be relatively similar to the reflection and moderate Islamic manhaj. Indonesian people should be pleased with their character, not avoid new things and not admit it to the extreme. In an effort to face the era of globalization, the Indonesian state must have the choice to produce human resources with high confidence and dedication. To create quality human resources, each individual prioritizes the formation and capacity that includes work behavior, discipline, obligation, and dependence based on the study of the Qur'an and Hadith.